2012
DOI: 10.5387/fms.58.78
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Usefulness of Non-Invasive Stroke Volume Variation Monitoring for Adjusting Fluid Supplementation During Laparoscopic Adrenalectomy in Patients With Pheochromocytoma

Abstract: : Purpose of the studyThe measurement of stroke volume variation (SVV) using the FloTrac TM system (Edwards Lifescience, USA) is useful to estimate cardiac preload. We evaluated the benefits of SVV monitoring for adjusting fluid supplementation during laparoscopic adrenalectomy under anesthesia in patients with pheochromocytoma. Subjects and MethodsAmong 10 patients who underwent laparoscopic adrenalectomy for pheochromocytoma in our institution from June 2004 to December 2009, SVV was not monitored in 5 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
0
6
0
5
Order By: Relevance
“…However, a case series of laparoscopic adrenalectomies in patients with pheochromocytoma demonstrated that both total infusion volume and urine output were significantly higher in the control group compared to the SVV-guided group (29). Total blood loss was similar between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, a case series of laparoscopic adrenalectomies in patients with pheochromocytoma demonstrated that both total infusion volume and urine output were significantly higher in the control group compared to the SVV-guided group (29). Total blood loss was similar between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the FloTrac system is useful for regulating the infusion volume. Isosu et al, have suggested that SVV measurement is useful for estimating the optional volume for fluid supplementation and may prevent excessive fluid infusion during surgical procedures, such as laparoscopic adrenalectomy in patients with pheochromocytoma (3). The recent report also reports the usefulness of fluid adjustment using Flotrac in many cancer surgery (4)(5)(6).…”
mentioning
confidence: 99%
“…The value of SVV is nevertheless reliable even when the circulating plasma volume is diminished [11], as it is based on the magnitude of respiratory fluctuation of arterial pressure. In our case, SVV occasionally fluttered in the first half of the surgery, but its course was largely consistent with that of ABP when the right adrenal gland vessels were being operated.…”
Section: Discussionmentioning
confidence: 99%